Patient and System Factors Related to Missed Opportunities for Screening in an Electronic Medical Record–driven, Opt‐out HIV Screening Program in the Emergency Department. (23rd September 2017) - Lin, Janet; Baghikar, Sara; Mauntel‐Medici, Cammeo; Heinert, Sara; Patel, Daven
Abstract: Objective: Emergency departments (EDs) have implemented HIV screening using a variety of strategies. This study investigates how specific patient and health system factors in the ED impact who is and is not screened in a combined targeted and nontargeted, electronic medical record (EMR)‐driven, opt‐out, HIV screening program. Methods: This was a retrospective, cross‐sectional study of ED visits where patients were determined eligible for HIV screening by an EMR algorithm between November 18, 2014, and July 15, 2015. The HIV screening workflow included three sequential events, all of which were required to get screened for HIV at the ED visit. The events were having a blood draw, being informed of the HIV screening policy by an ED nurse at the point of blood draw, and the patient consenting to the HIV test. Each event represented a dichotomous outcome and its association with six patient factors (age, sex, race/ethnicity, marital status, preferred language, and Emergency Severity Index [ESI]) and two health system factors (ED crowding and program phase) was investigated using multivariable modeling. Results: A total of 15, 918 ED visits were analyzed. Blood was drawn in 8, 388 of 15, 918 visits (53%). Of 8, 388 visits where blood was drawn, there were 5, 947 (71%) visits where ED nurses documented informing patients of the HIV screening policy. Of those visits, patient consent to the HIV test was documented at 3, 815 (64%) visits. Patients between 13 and 19 years of age were significantly less likely to have blood drawn, to be informed of the screening policy, and to consent to the HIV test compared to other age groups. Both ED crowding and a patient's ESI were associated with decreased odds of having a blood draw and being informed of HIV screening by an ED nurse, but showed no association with patients consenting to the HIV test. Conclusion: Many patients, particularly adolescents and young adults, are missed in ED HIV screening programs that require blood draw and depend on providers to obtain consent for testing. To ensure that these patients are reached, future ED screening programs should strive to develop innovative workflows that allow for blood draws for HIV screening only and streamline the processes of obtaining informed consent and ordering tests for all eligible patients.